1985
DOI: 10.1152/ajpgi.1985.249.6.g761
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin receptors in normal and malignant gastrointestinal mucosa: age-associated changes

Abstract: Synthetic human gastrin 17-I (MG) and an analogue, [Leu15]gastrin-17-I (LG), were radiolabeled with Na125I by Iodo-Gen, EnzymoBead, and chloramine-T methods, and the characteristics of the radiolabeled peptides were determined. When 125I-MG was iodinated by chloramine-T, its biological activity and its binding activity were almost abolished, whereas the biological activity of 125I-LG, iodinated by either of the methods, and of 125I-MG, iodinated by Iodo-Gen and EnzymoBeads, was not significantly affected. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…In fact, we have observed that aging is associated with a loss of responsiveness of the gastric mucosa to the trophic action of both gastrin and bombesin (46,51), while EGF and TGF-α actually inhibit mucosal proliferative activity in aged rats (47,52). Although reasons for this are not fully understood, the age-related loss of responsiveness of the gastric mucosa to the trophic action of gastrin could be related in part to a decrease in the number of gastrin binding sites in the gastric mucosa (54). Whether a similar phenomenon is responsible for the age-related loss of the trophic action of bombesin in the gastric mucosa remains to be determined.…”
Section: Stomachmentioning
confidence: 99%
“…In fact, we have observed that aging is associated with a loss of responsiveness of the gastric mucosa to the trophic action of both gastrin and bombesin (46,51), while EGF and TGF-α actually inhibit mucosal proliferative activity in aged rats (47,52). Although reasons for this are not fully understood, the age-related loss of responsiveness of the gastric mucosa to the trophic action of gastrin could be related in part to a decrease in the number of gastrin binding sites in the gastric mucosa (54). Whether a similar phenomenon is responsible for the age-related loss of the trophic action of bombesin in the gastric mucosa remains to be determined.…”
Section: Stomachmentioning
confidence: 99%
“…In addition, gastrin stimulates the growth of some colon [5][6][7][8][9], gastric [10,11] and pancreatic cancers [12,13] in vitro (cell lines) and in vivo (xenotransplanted cancers, chemically induced tumours in rats and in mice). These effects are receptor-mediated: specific gastrinbinding sites were shown to be present on normal gastrointestinal mucosa [14][15][16] and on some human and murine gastric, colonic and pancreatic carcinomas [6,14,17]. DMH Gastrin receptor antagonist have been hypothesized to be of clinical relevance in the treatment of gastrin-sensitive colorectal tumours [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…CCK agonists and antagonists acting at central CCKB receptors respectively block and enhance opiate-induced analgesia (13). CCKB-type receptors have also been described outside the CNS in gastrointestinal smooth muscle cells (14), where they modulate gallbladder and bowel motility; and in guinea pig (15) and dog pancreas (16) and various neoplastic tissues [such as human stomach, colon (17), and lung carcinomas (18), and the rat pancreatic acinar carcinoma cell line AR42-J (19)], where they may regulate cell growth. The presence of CCKB receptors on peripheral lymphocytes and monocytes and monocyte-derived splenic cells suggests that CCK may play a role in the long-suspected neuroendocrine modulation of the immune system (20,21).…”
mentioning
confidence: 99%